2022
DOI: 10.1021/acs.jproteome.2c00009
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Survey of the Regulatory Networks of the Long Noncoding RNA BANCR in Cervical Cancer Cells

Abstract: Long noncoding RNAs (lncRNAs) are increasingly recognized as functional regulators of human cancers. BRAF-activated noncoding RNA (BANCR), an oncogenic lncRNA, has a carcinogenic effect on many types of cancers. However, the clinical significance and molecular mechanisms of BANCR in cervical cancer are still unclear. Here, we generated BANCR knockout cell lines via CRISPR/Cas9 editing and revealed that BANCR plays roles in the apoptosis, proliferation, and migration of HeLa cells. A quantitative proteomics str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 82 publications
(130 reference statements)
0
5
0
Order By: Relevance
“…BANCR is a 693 bp transcript located on chromosome 9 and has been implicated in a variety of biological processes, such as cell proliferation, migration, and invasion. However, the exact role of BANCR in cancer remains a subject of debate and further investigation 6–9 . In addition to its involvement in cancer, BANCR has also been implicated in autoimmune disorders such as HT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BANCR is a 693 bp transcript located on chromosome 9 and has been implicated in a variety of biological processes, such as cell proliferation, migration, and invasion. However, the exact role of BANCR in cancer remains a subject of debate and further investigation 6–9 . In addition to its involvement in cancer, BANCR has also been implicated in autoimmune disorders such as HT.…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact role of BANCR in cancer remains a subject of debate and further investigation. [6][7][8][9] In addition to its involvement in cancer, BANCR has also been implicated in autoimmune disorders such as HT. It has been observed that individuals with HT have an elevated risk of developing PTC compared to the general population.…”
mentioning
confidence: 99%
“…A previous study clarified that LINC00586 induces the migration of CRC cells and promotes the process of EMT ( Guo et al, 2014 ). Of note, researchers performed quantitative proteomics strategy to globally identify LINC00586-regulated proteins in HeLa cells and found 569 differentially expressed proteins (DEPs) in HeLa cells upon knockout of BANCR ( Wang et al, 2022 ). Nevertheless, the detailed molecular mechanism underlying LINC00586 waits to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…CAMP‐response element‐binding protein 1 (Creb1) encodes a transcription factor that binds as a homodimer to the cAMP‐responsive element. The phosphorylated status of Creb1 can induce gene transcription to respond to hormonal stimulation of the cAMP pathway 20 . In ischemia‐related studies, Creb1 correlated with the ischemic injury and ischemia–reperfusion injury process in various tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylated status of Creb1 can induce gene transcription to respond to hormonal stimulation of the cAMP pathway. 20 In ischemia‐related studies, Creb1 correlated with the ischemic injury and ischemia–reperfusion injury process in various tissues. For example, in the mouse hindlimb muscle ischemic tissue, JNK3 deletion is involved in the upregulated vascular remodeling response during peripheral ischemia through the activation of Creb1, leading to the upregulation of various growth factors in the ischemic muscles.…”
Section: Introductionmentioning
confidence: 99%